PRAGMATIC FEATURES OF SPOUSAL INTERACTION IN ENGLISH AND UZBEK FAMILY DISCOURSE - Azimova Shahrinoz Ikromovna (International Journal of Literature and Language Studies, 2026)
The present study examines the pragmatic features of spousal interaction in English and Uzbek family discourse. Family discourse serves as one of the primary environments where interpersonal relationships, social values, and cultural norms are constructed and maintained through language. The research focuses on speech acts, politeness strategies, implicatures, forms of address, and communicative strategies employed by spouses in everyday communication. A comparative discourse-pragmatic analysis was conducted on authentic conversational samples derived from English and Uzbek family interactions.